The Impacts of Supply Chain Ambidexterity and Resource Flexibility on Supply Chain Resilience in Manufacturing SMES in Bandung, Indonesia - Jamaludin, Maun; Yuniarti, Yuyun; Rustandi, Iyus; Sumiati, Imas; Oktavian, Alif (Jurnal Manajemen & Agribisnis, 2023)
The supply chain, which is an important part of business and production operations, can help manufacturing SMEs increase their competitiveness and strengthen their position in the market. The purpose of this study is to analyze the effect of extraordinary agility and resource flexibility on supply chain resilience. The research method used is a quantitative approach with the analysis technique Partial Least Square-Structural Equation Modeling (PLS-SEM). The number of samples used in this study was 194 respondents, chosen through a simple random sampling technique. The results show that resource flexibility has a positive effect on supply chain agility and streamlining. Supply chain agility also has a positive and significant impact on supply chain resilience, while lean supply chain cannot mediate this relationship. Finally, an agile supply chain also mediates the relationship between resource flexibility and supply chain resilience. The results of this study can be used as a reference for manufacturing SMEs in developing effective supply chain management strategies to increase their supply chain resilience. Keywords: agile supply chain, lean supply chain, resource flexibility, supply chain ambidexterity, supply chain resilience